Research on Rheology and Micro-properties of Modified Room Temperature Biological Asphalt. Issue 1 (January 2022) - Shi, Yang; Wang, Wen; Guo, Liujie; Li, Jiusu
Abstract: In order to explore the rheological property and principles of modified room temperature biological asphalt made with petroleum asphalt, vegetable asphalt, and unsaturated fatty acids as raw materials, waste rubber powder as modifier, and calcium hydroxide powder as curing agent, this paper compared and tested the rheological properties and the original petroleum asphalt by using DSR and BBR, and the micro-properties of the asphalt were studied by using SEM. The PG classification of modified room temperature biological asphalt has been upgraded from PG58-28 of the original petroleum asphalt to PG82-28. Compared with the original petroleum asphalt, the high temperature rheological property of the modified room temperature biological asphalt has been greatly improved. Its low temperature rheological property is equivalent to the original one, but the possibility of cracking is lower. SEM test showed that the components of the modified room temperature biological asphalt are well combined. The calcium hydroxide curing agent reacts with fatty acid and the rubber particles cross link with each other to form a mesh package in the asphalt, which provides strength for the modified temperature biologic asphalt at room temperature.